Development of an interactive e-module based on pbl to enhance elementary students' critical thinking - Cahyaningsih, Ujiati; Nahdi, Dede Salim (Prodi PGSD FKIP Universitas Islam Sultan Agung, 2025)
The development of critical thinking skills at the elementary school level is a foundational component in preparing students to navigate complex, real-world problems that demand analytical reasoning, evaluative judgment, and effective problem-solving. This study investigates the efficacy of an interactive e-module grounded in Problem-Based Learning (PBL) principles in enhancing the critical thinking abilities of fourth-grade students, with a particular focus on mathematics and science instruction. A quasi-experimental design was implemented, comprising an experimental group that utilized the PBL-based e-module and a control group that received conventional instruction. Data collection methods encompassed pre- and post-tests measuring critical thinking performance, observational protocols documenting student interaction with the module, student perception questionnaires, and semi-structured interviews with both students and teachers to elicit qualitative insights. The findings indicate that students in the experimental group exhibited significantly greater gains in critical thinking skills, as evidenced by a substantial improvement between pre- and post-test scores. Moreover, these students engaged more actively in collaborative discussions and problem-solving tasks relative to their peers in the control group. The results underscore the effectiveness of PBL-based e-modules as pedagogical tools for fostering critical thinking at the elementary level. The study's implications point to the transformative potential of integrating PBL frameworks into digital learning environments to enhance educational quality and student engagement in primary education settings